MICROBIAL QUALITY ASSESSMENT OF EDIBLE GREEN VEGETABLES AND THE EFFICACY OF HOUSEHOLD ANTISEPTIC PRODUCTS FOR MICROORGANISM ELIMINATION - Rodriguez , Dr. Maria Elena; Martinez, Mr. Carlos Javier (Advanced Journal of Environmental Sciences (AJES), 2023)
Green leafy vegetables are essential components of a balanced diet, rich in vital vitamins and minerals. However, concerns arise from the potential contamination of both imported and locally grown green leafy vegetables, making them a primary source of foodborne pathogens. Contamination can result from various factors, including the use of natural organic fertilizers, tainted irrigation water, direct exposure to livestock, wild animals, and birds, as well as inadequate food handler hygiene practices. This contamination poses a significant risk of entero-pathogenic infections, particularly from pathogens such as Escherichia coli and Salmonella. Escherichia coli encompasses a range of strains, with most being nonpathogenic and naturally occurring in the intestinal tracts of animals, including humans. However, certain strains, such as O157:H7, produce potent toxins that can cause severe intestinal damage, leading to life-threatening conditions. Salmonella, on the other hand, represents a group of bacteria responsible for Salmonella infection, leading to various intestinal illnesses, including typhoid fever, food poisoning, gastroenteritis, and enteric fever.